2011
DOI: 10.1111/j.1600-0765.2011.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes produce tumor necrosis factor‐α and interleukin‐6 in response to Porphyromonas gingivalis

Abstract: The results obtained in the present study show that P. gingivalis extract induces TNF-α and IL-6 in an in vitro liver model and that macrophage-derived TNF-α mediates the induction of TNF-α in hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Many proinflammatory cytokine receptors such as IL-6 receptor, TNF-α receptor, IL-1β receptor, and IFN-γ receptor are expressed in hepatocytes. Although several reports showed that hepatocytes can produce these inflammatory cytokines under certain conditions 35 , 36 , innate immune cells, especially Kupffer cells in the liver are believed to the main source of proinflammatory cytokines during acute infections 16 , 37 . We tried to verify whether similar things happen to DAMPs.…”
Section: Resultsmentioning
confidence: 99%
“…Many proinflammatory cytokine receptors such as IL-6 receptor, TNF-α receptor, IL-1β receptor, and IFN-γ receptor are expressed in hepatocytes. Although several reports showed that hepatocytes can produce these inflammatory cytokines under certain conditions 35 , 36 , innate immune cells, especially Kupffer cells in the liver are believed to the main source of proinflammatory cytokines during acute infections 16 , 37 . We tried to verify whether similar things happen to DAMPs.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no TNF‐α release from Hepa 1–6 cells, which is in agreement with the observation that under in vitro conditions hepatocytes (Hepa 1–6 cells) can only produce TNF‐α production during co‐culture with macrophages. [ 64 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent investigations have indicated that this is in fact not the case. Hepatocytes mount a robust response to challenge with either LPS or IL-1b to produce key inflammatory cytokines, including IL-6, TNFa, and IL-1b (Liu et al, 2002;Panesar et al, 1999;Spencer et al, 2013;Takano et al, 2012;Yoshigai et al, 2014). It is also now well known that hepatocytes express all the necessary machinery to respond to bacterial sepsis , TABLE 5 Expression level of IL-1b, IL-6, TNFa, and IL1-Ra in wild-type and PXR-KO PCHs PCHs isolated from wild-type (n = 6) or PXR-KO mice (n = 6) were pretreated for 24 hours with either vehicle (0.1% dimethylsulfoxide) or PCN (10 mM).…”
Section: Discussionmentioning
confidence: 99%